2010
DOI: 10.1089/end.2009.0184
|View full text |Cite
|
Sign up to set email alerts
|

First Prize: Characterization of Renal Ischemia Using DLP®Hyperspectral Imaging: A Pilot Study Comparing Artery-Only Occlusion Versus Artery and Vein Occlusion

Abstract: In this pilot study, we demonstrate that renal tissue oxygenation drops rapidly after occlusion of the renal vasculature and returns to near baseline 30 minutes after reperfusion. In the porcine model, the %HbO(2) differs significantly between AO and AV occlusion for up to 35 minutes after ischemia onset, indicating a possible "ischemic window" in which AO occlusion may provide benefit over AV occlusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 15 publications
0
34
0
Order By: Relevance
“…Previous works in this field evaluated tissue perfusion of in vivo perfused kidneys and proposed HSI for postoperative assessment Tracy et al, 2010;Holzer et al, 2011;Zuzak et al, 2011;Crane et al, 2008). In addition to the characterization of water-enriched tissue around 970 nm, the analysis of lipid-sensitive regions in the spectral NIR band might be interesting for the correlation with ischemic injury (van Veen et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Previous works in this field evaluated tissue perfusion of in vivo perfused kidneys and proposed HSI for postoperative assessment Tracy et al, 2010;Holzer et al, 2011;Zuzak et al, 2011;Crane et al, 2008). In addition to the characterization of water-enriched tissue around 970 nm, the analysis of lipid-sensitive regions in the spectral NIR band might be interesting for the correlation with ischemic injury (van Veen et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…13 Additionally, 3-CCD contrast enhancement was used to compare renal oxygenation post-reperfusion to renal oxygenation before hilar clamping. 13 Zuzak and coworkers 30,31 have monitored tissue oxygenation intraoperatively with a DLP® hyperspectral imaging system, at near-video frame rates, to study the effects of artery-only clamping and ice slush application on renal oxygenation. 32 Their results indicated that artery-only clamping and 7-10 min of ice slush application can help to minimize the decrease in renal oxygenation during partial nephrectomies.…”
Section: Discussionmentioning
confidence: 99%
“…Studies by other researchers have also demonstrated the effectiveness of this approach for assessing perfusion of the retina, 7 brain, 8 and kidneys. 9 Spectral reflectance imaging has also been used to investigate cold and warm ischaemia-reperfusion injury on the kidneys.…”
Section: Optical Imaging Of Hemodynamicsmentioning
confidence: 99%